Uji Mikrobiologi Sumber Air Perumahan Bank Tabungan Negara (BTN) Sosial Sentani Kabupaten Jayapura - John Yoro Parlindungan; Nova Riama Lumban Raja; Novike Bela Sumanik (Musamus Journal of Science Education, 2020)
This study purposes to analyze the levels of coliform bacterial contamination and coliform bacteria types in water sources used by population in BTN Sosial housing in Jayapura Regency. The method used is the MPN method (Most Probable Number) and biochemical test methods. The results of the examination showed that there were <3 cells / 100 ml in the spring, 2300 cells / 100 ml of water flow, and in 24,000 cell / 100 ml water samples. The types of coliform bacteria found in the water sources are Citrobacterfreundii and Serratiamarcescens. Based on the results of the examination, it can be concluded that the water used by the people in the BTN Sosial housing contaminated with coliform bacteria exceeds the limit set by the Minister of Health of the Republic of Indonesia and needs further treatment to be consumed.